William James's Objection to Epiphenomenalism. Issue 4 (December 2019) - Klein, Alexander
Abstract : James developed an evolutionary objection to epiphenomenalism that is still discussed today. Epiphenomenalists have offered responses that do not grasp its full depth. I thus offer a new reading and assessment of James's objection. Our life-essential, phenomenal pleasures and pains have three features that suggest that they were shaped by selection, according to James: they are natively patterned, those patterns are systematically linked with antecedent brain states, and the patterns are "universal" among humans. If epiphenomenalism were true, phenomenal patterns could not have been selected (because epiphenomenalism precludes phenomenal consciousness affecting reproductive success). So epiphenomenalism is likely false.